GRT suínos: risk management system for thermal comfort in pigs - Bueno, Fabiano Gregolin de Campos (2023)
Pig production is subject to various factors that limit production efficiency, with climatic environment being among the most significant. Seeking alternatives to minimize the animals\' thermal challenge is essential, making swine producers\' managerial activity highly complex. In this sense, an area that can offer significant support in swine producers\' decision-making is risk management. In pig farming, as in all agricultural activities, risks are inherent and involve all stages of the production process. Research focused on risk management is abundant but directed towards specific themes. However, research aimed at risk management in pig thermal comfort, with an integrative approach, is an unexplored field. The purpose of this study was to develop the Thermal Risk Management in pigs GRT Suínos. Therefore, the study was divided into three stages. The first was a systematic review to find the state of the art in risk management in pigs. The second stage consisted of creating a tool that guides producers in identifying risks in pig thermal comfort, adopting a constructivist approach with the creation of a new model based on an extensive literature review and empirical data, resulting in a map of risks in pig thermal comfort. The third stage aimed to create, develop, and validate the GRT Suínos, developed on the Android operating system, based on the Scrum method. The results demonstrated that GRT Suínos is an innovative resource that allows producers and technicians to manage thermal risks in pigs, with its acceptability proven by the high user satisfaction rate and good usability. GRT Suínos represents an important innovation in the integration of risk management in the field of pig farming, contributing to the improvement of productive conditions for both humans and animals, thus opening up a vast field for future research.